Histopathological changes in lungs, liver and kidneys in cases of death due to agricultural poisoning in a tertiary care centre: A cross sectional study - Dr Siddesh, R C; Dey , Biswajit (Journal of Indian Academy of Forensic Medicine, 2021)
Medico legal deaths due to agricultural poisoning claim a substantial number of lives in Andaman and Nicobar Islands. Respiratory failure is the most common complication of OP poisoning leading to death. Histopathological studies of viscera in organophosphate poisoning cases help the autopsy surgeon in ascertaining out the secondary causes of death. Microscopy of three visceral organs lungs, liver and kidneys of 40 cases of organophosphate poisoning were studied and the changes were correlated with the duration of survival post consumption. By knowing the exact histopathological changes in these organs, it is easier to attribute death to a failure of one of these organs as a consequence of organophosphate consumption. Knowing the rapidity of involvement of an organ is beneficial to the treating physician as well thereby helping him reduce the morbidity and hence mortality.